2015
DOI: 10.1128/aem.00557-15
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Bacterial Communities to Simulated Climate Changes in Alpine Meadow Soil of the Qinghai-Tibet Plateau

Abstract: e The soil microbial community plays an important role in terrestrial carbon and nitrogen cycling. However, microbial responses to climate warming or cooling remain poorly understood, limiting our ability to predict the consequences of future climate changes. To address this issue, it is critical to identify microbes sensitive to climate change and key driving factors shifting microbial communities. In this study, alpine soil transplant experiments were conducted downward or upward along an elevation gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 36 publications
6
61
0
Order By: Relevance
“…The observed significant negative rank-based correlation between increasing temperature and total cell counts (TCCs) contradicts our hypothesis that millennial-scale permafrost warming directly increases microbial abundance. It is, however, in line with related studies on arctic and subarctic soil microbial communities in which a negative effect of increasing temperature on microbial abundance was assigned to freeze-thaw cycles (Schimel et al, 2007;Skogland et al, 1988) and substrate depletion (Walker et al, 2018). Both effects are, however, unlikely here.…”
Section: Discussionsupporting
confidence: 92%
“…The observed significant negative rank-based correlation between increasing temperature and total cell counts (TCCs) contradicts our hypothesis that millennial-scale permafrost warming directly increases microbial abundance. It is, however, in line with related studies on arctic and subarctic soil microbial communities in which a negative effect of increasing temperature on microbial abundance was assigned to freeze-thaw cycles (Schimel et al, 2007;Skogland et al, 1988) and substrate depletion (Walker et al, 2018). Both effects are, however, unlikely here.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is suggested that reciprocal translocation experiment is the most rigorous way of demonstrating impacts of climate change because this experiment allows applying both warming and cooling processes and is believed to reduce chemical and mechanical disturbances to a minimum29. Several reciprocal translocation experiments have been conducted on plant survival and productivity30, soil properties and respiration2934, and soil microbial community333536 in natural grassland ecosystems. However, the AM fungal response to soil-plant reciprocal translocation along an altitudinal gradient remains largely unexplored.…”
mentioning
confidence: 99%
“…This implies that the observed patterns in bacterial community composition may, to a certain extent, be explained by the decrease in abundance of Betaproteobacteria. Several other studies have reported a consistent response to environmental drivers, including temperature elevation, for Betaproteobacteria (Fierer et al 2007;Rui et al 2015;Zhang et al 2016) indicating that members of this group may largely share environmental requirements.…”
Section: The Response Of High-level Microbial Groups To Warmingmentioning
confidence: 66%
“…Given the recent concern regarding the stability of ecological systems under a changing climate, there 63 have been numerous studies investigating the effects of warming on microbial community composition 64 (Zogg et al 1997;Zhang et al 2005;Frey et al 2008;Weedon et al 2012;Luo et al 2014;Karhu et al 65 2014;Xu et al 2015;Rui et al 2015). The rationale behind these studies is that sensitivity of soil 66 microbial community composition to increasing soil temperatures will indicate a corresponding 67 sensitivity of the biogeochemical processes these communities are involved in (Zogg et al 1997;68 Strickland et al 2009).…”
Section: Introduction 61 62mentioning
confidence: 99%